Beneficial Effects of 6-Month Supplementation with Omega-3 Acids on Selected Inflammatory Markers in Patients with Chronic Kidney Disease Stages 1–3 - Pluta, Agnieszka (Biomed Res Int, 2017)
INTRODUCTION: Chronic kidney disease (CKD) is accompanied by inflammation. The aim of this study was to evaluate the effect of 6-month supplementation with omega-3 acids on selected markers of inflammation in patients with CKD stages 1–3. METHODS: Six-month supplementation with omega-3 acids (2 g/day) was administered to 87 CKD patients and to 27 healthy individuals. At baseline and after follow-up, blood was taken for C-reactive protein (CRP) and monocyte chemotactic protein-1 (MCP-1) concentration and white blood cell (WBC) count. Serum concentration of omega-3 acids—eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and alpha-linolenic acid (ALA)—was determined using gas chromatography. And 24-hour urinary collection was performed to measure MCP-1 excretion. RESULTS: After six-month omega-3 supplementation, ALA concentration increased in CKD patients and in the reference group, while EPA and DHA did not change. At follow-up, a significant decrease in urinary MCP-1 excretion in CKD (p = 0.0012) and in the reference group (p = 0.001) was found. CRP, serum MCP-1, and WBC did not change significantly. The estimated glomerular filtration rate (eGFR) did not change significantly in the CKD group. CONCLUSIONS: The reduction of urinary MCP-1 excretion in the absence of MCP-1 serum concentration may suggest a beneficial effect of omega-3 supplementation on tubular MCP-1 production. TRIAL REGISTRATION: This study was registered in ClinicalTrials.gov (identifier: NCT02147002).